Early Christianity in Pompeian light : people, texts, situations - Longenecker, Bruce W (Minneapolis, MN : Fortress Press, 2016)
Scholars of early Christianity are awakening to the potential of Pompeii's treasures for casting light on the settings and situations that were commonplace and conventional for the first urban Christians. The uncovered world of Pompeii, destroyed by the eruption of Mount Vesuvius in 79 C.E., allows us to peer back in time, capturing a heightened sense of what life was like on the ground in the first century -- the very time when the early Jesus-movement was beginning to find its feet. In light of the Vesuvian material remains, historians are beginning to ask fresh questions of early Christian texts and perceive new contours, nuances, and subtleties within the situations those texts address. The essays of this book explore different dimensions of Pompeii's potential to refine our lenses for interpreting the texts and situations of early Christianity. The contributors to this book (including Carolyn Osiek, David Balch, Peter Oakes, Bruce Longenecker, and others) demonstrate that it is an exciting time to explore the interface between the Vesuvian contexts and the early Jesus-movement. - from back of book
pt. I. Envisioning situations. 1. Growing up female in the Pauline churches: what did she do all day? / Carolyn Osiek -- 2. Nine types of church in nine types of space in the Insula of the Menander / Peter Oakes -- 3. The empress, the goddess, and the earthquake: atmospheric conditions pertaining to Jesus-devotion in Pompeii / Bruce W. Longenecker -- pt. II. Enhancing texts. 4. Powers and protection in Pompeii and Paul: the apotropaic function of the cross in the Letter to the Galatians / Natalie R. Webb -- 5. Violence in Pompeian/Roman domestic art as a visual context for Pauline and Deutero-Pauline letters / David L. Balch -- 9. Spheres and trajectories: the angels of the churches (Revelation 1-3) in context / Jeremiah N. Bailey
Includes bibliographical references (pages 201-240) and indexes
Keywords: Church history -- 2nd century; Pompeii (Extinct city)